2018
DOI: 10.1002/ejoc.201800578
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Sequential Bromination and Fluorination to Access 3‐Fluoroimidazo[1,2‐a]pyridines from Arylketones

Abstract: 3‐Fluoro‐2‐arylimidazo[1,2‐a]pyridines were selectively synthesised in one‐pot from acetophenones and 2‐aminopyridines under mild conditions. The sequence of reactions involved bromination, condensation, and late‐stage fluorination. Two halogenating reagents play key roles in the process. We found that tetrabutylammonium tribromide and SelectfluorTM gave excellent yields of the desired products in the one‐pot sequential reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The synthesis of imidazo[1,2‐ a ]pyridine core containing a mono‐halogen substituent at the 3‐position by the condensation of an α ‐halo aryl ketone with a 2‐aminopyridine is still quite difficult [223] . To develop a new fluorination method to synthesize 3‐fluoroimidazo[1,2‐ a ]pyridine, Udavant et al [224] . in 2018 reported an efficient one‐pot method for the regioselective synthesis of 3‐fluoro‐2‐phenylimidazo[1,2‐ a ]pyridines 295 from aryl ketones 293 and 2‐aminopyridine derivatives 294 in protic media in good to excellent yields.…”
Section: Development Of Various Methods Towards the Synthesis Of Imid...mentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of imidazo[1,2‐ a ]pyridine core containing a mono‐halogen substituent at the 3‐position by the condensation of an α ‐halo aryl ketone with a 2‐aminopyridine is still quite difficult [223] . To develop a new fluorination method to synthesize 3‐fluoroimidazo[1,2‐ a ]pyridine, Udavant et al [224] . in 2018 reported an efficient one‐pot method for the regioselective synthesis of 3‐fluoro‐2‐phenylimidazo[1,2‐ a ]pyridines 295 from aryl ketones 293 and 2‐aminopyridine derivatives 294 in protic media in good to excellent yields.…”
Section: Development Of Various Methods Towards the Synthesis Of Imid...mentioning
confidence: 99%
“…[221] To develop a green approach for the synthesis of biologically important heterocycles, Tufail et al [222] in 2017 reported a regioselective green approach to synthesize 2-aryl substituted imidazo[1,2- The synthesis of imidazo[1,2-a]pyridine core containing a mono-halogen substituent at the 3-position by the condensation of an α-halo aryl ketone with a 2-aminopyridine is still quite difficult. [223] To develop a new fluorination method to synthesize 3-fluoroimidazo[1,2-a]pyridine, Udavant et al [224] Inorganic solids have versatile properties such as their high thermal stability, ease of handling, and ability of H-bond formation with fluoride ions. So they have gained significant attention from chemists towards organic synthesis.…”
Section: Chemistryselectmentioning
confidence: 99%
“…64 Shinde and co-workers reported the synthesis of pyridine containing imidazole moieties from arylethyl ketones. 65 The bromination of arylketone gave the phenacyl bromides in reaction with aminopyridine followed by cyclization provided the imidazolium pyridine which in the later stage was fluorinated using selectfluor. Several derivatives of fluorinated imidazoles Scheme 12 Synthesis of n-tetrabutylammonium tribromide using potassium bromide.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…In the past 20 years, with the development of the chemical and pharmaceutical industries, novel approaches to the synthesis of heterocycles have rapidly emerged. The development of more green and effective methods to heterocycle synthesis has been a major research interest for green and sustainable chemists because more than 70% of major commercially available synthetic drugs contain at least one N -fused heterocyclic scaffold. It is worth mentioning that the imidazo­[1,2-α]­pyridine derivatives exhibit a wide range of biological and pharmacological activities, such as antibacterial, antiulcer, antiviral, and antitumor (Scheme ). As a result, tremendous efforts have been devoted to the synthesis and functionalization of N -fused heterocyclic scaffolds. Among them, 3-halo imidazo­[1,2-α]­pyridines are great potential intermediates for their diverse reactivity in many types of reactions.…”
Section: Introductionmentioning
confidence: 99%